2016
DOI: 10.3311/ppso.8871
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance Factors in the Small and Medium-sized Enterprises

Abstract: The analysis of the problem of work-life balance (WLB) expanded through the last few years, being transformed from the typically female problem, connected with family life, into more general issue, concerning all the employees. The problem occurs especially with reference to the small and medium enterprises (SMEs), which dominate in the enterprise structure in the world. At the same time these organizations represent relatively low standards in terms of realization of the basic rules of HR management, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Similarly, also Lačný (2013) emphasizes that mutual trust between employees is a prerequisite for the voluntary identification of employees with the organization, its goals and vision. Interestingly, ethical leadership contains all major factors that are related to employee work-life balance, such as good relations with supervisor, pleasant atmosphere at workplace, open communication and active listening to the needs of employees (on WLB see for instance Robak et al, 2016).…”
Section: Nature and Consequences Of Ethical Leadershipmentioning
confidence: 99%
“…Similarly, also Lačný (2013) emphasizes that mutual trust between employees is a prerequisite for the voluntary identification of employees with the organization, its goals and vision. Interestingly, ethical leadership contains all major factors that are related to employee work-life balance, such as good relations with supervisor, pleasant atmosphere at workplace, open communication and active listening to the needs of employees (on WLB see for instance Robak et al, 2016).…”
Section: Nature and Consequences Of Ethical Leadershipmentioning
confidence: 99%
“…Thus, for instance, fathers whose children were born before 2010 were not entitled to paternity leave and some may be still not aware of such a solution. Similarly, Robak and Słocińska [9] showed that almost 80% of the studied Polish workers declared the awareness of the available organizational and legal WLB benefits, yet, 20% of them claimed that employee rights were not obeyed in their companies.…”
Section: Availability Of Wlb Benefitsmentioning
confidence: 91%
“…This finding is even more affirmative if we consider that most of the surveyed employers belong to the segment of micro and small enterprises, which are expected to have a sporadic rather than a systemic approach to this topic. An explanation for this can be found in the research of Robak et al (2016) IJSSP 40,9/10 internal personnel relations, influencing most strongly the employees' abilities in maintaining WLB, were most favourable in micro and small companies due to the small number of employees and simple organisational structure. One of the surveyed HR Managers explains it in the following way: "We are a small company, so we achieve everything by agreement", pointing to the existence of informal business practices, but also to the room to manoeuvre when applying flexibility in small enterprises in crises such as COVID-19.…”
Section: Family-friendly Workplace Practices: Friend or Foe To The Children?mentioning
confidence: 98%